Alpha9Alpha10 Nicotinic Acetylcholine Receptors as Target for the Treatment of Chronic Pain - Del Bufalo, Alessandra; Cesario, Alfredo; Salinaro, Gianluca; Fini, Massimo; Russo, Patrizia (Current Pharmaceutical Design, 2014)
Chronic pain is a widespread healthcare problem affecting not only the patient but in many ways all the society. Chronic pain is a disease itself that endures for a long period of time and it is resistant to the majority of medical treatments that provide modest improvements in pain and minimum improvements in physical and emotional functioning. More co-existing chronic pain conditions may be present in the same individual (patient). The α9α10 nicotinic acetylcholine receptor (nAChR) may be a potential target in the pathophysiology of chronic pain, as well in the development of breast and lung cancers. α-conotoxins (α-CNT) are small peptides used offensively by carnivorous marine snails known as Conus that target nAChR. Among α-CNT there are potent and selective antagonists of α9α10 nAChR such as RgIA and Vc1.1 that produces both acute and long lasting analgesia. Moreover, these peptides accelerate the recovery of nerve function after injury, likely through immune/inflammatory-mediated mechanisms. We review the background, findings, implications and problems in using compounds that act on 910 nAChR.
Keywords: α9α10 nAChR